2020
DOI: 10.3389/fphys.2020.00120
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative and Dynamic MRI Measures of Peripheral Vascular Function

Abstract: The endothelium regulates and mediates vascular homeostasis, allowing for dynamic changes of blood flow in response to mechanical and chemical stimuli. Endothelial dysfunction underlies many diseases and is purported to be the earliest pathologic change in the progression of atherosclerotic disease. Peripheral vascular function can be interrogated by measuring the response kinetics following induced ischemia or exercise. In the presence of endothelial dysfunction, there is a blunting and delay of the hyperemic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 105 publications
(126 reference statements)
0
13
0
Order By: Relevance
“…In the case of endothelial dysfunction and structural dysfunction, vascular hyperemia becomes blunted and can be measured noninvasively by a variety of quantitative MRI methods, including a blood oxygenation-level-dependent (BOLD) signal that reflects the combined effect of blood flow and capillary bed oxygen content, arterial spin labeling (ASL) for quantification of regional perfusion, phase contrast (PC) to quantify arterial flow waveforms, macrovascular blood flow velocity and rate, etc . [ 17 ] In the development of vascular aging, BOLD MRI can also be observed even in the absence of obvious ASCVD. [ 18 , 19 ] Some studies have also found that there is an association between ASL-based measurement and the occurrence and severity of peripheral vascular disease.…”
Section: Structural Assessment Of Vascular Agingmentioning
confidence: 99%
“…In the case of endothelial dysfunction and structural dysfunction, vascular hyperemia becomes blunted and can be measured noninvasively by a variety of quantitative MRI methods, including a blood oxygenation-level-dependent (BOLD) signal that reflects the combined effect of blood flow and capillary bed oxygen content, arterial spin labeling (ASL) for quantification of regional perfusion, phase contrast (PC) to quantify arterial flow waveforms, macrovascular blood flow velocity and rate, etc . [ 17 ] In the development of vascular aging, BOLD MRI can also be observed even in the absence of obvious ASCVD. [ 18 , 19 ] Some studies have also found that there is an association between ASL-based measurement and the occurrence and severity of peripheral vascular disease.…”
Section: Structural Assessment Of Vascular Agingmentioning
confidence: 99%
“…For BOLD MRI, several review papers were already published and described technical details with numerous applications in functional MRI [ 80 , 81 , 82 ]. Paramagnetic deoxyhemoglobin has a ferrous iron on the heme.…”
Section: Mri Based Oxygenation Imagingmentioning
confidence: 99%
“…Even magnetic resonance imaging (MRI) has been increasingly used for assessing endothelial functioning [ 71 ]. Quantitative, dynamic, non-contrast MRI studies have been developed, including the blood oxygen level-dependent (BOLD) imaging, the arterial spin labelling (ASL), the phase contrast (PC), the MRI-measured PWV, the luminal FMD, and the dynamic MRI oximetry [ 71 ]. These innovative approaches provided the opportunity to measure endothelial dysfunctions in human sites not easily accessible.…”
Section: How To Measure Endothelial Dysfunction: Direct and Indirementioning
confidence: 99%